Społeczna odpowiedzialność w strategii przedsiębiorstw sektora TSL notowanych na FWB i GPW - Anna Dada (Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2022)
The article aims to evaluate the implementation of the concept of corporate social responsibility in the strategy in selected enterprises from the TSL sector and to indicate one of the key challenges, which is the effective presentation of CSR policy. The research covered 7 companies listed on the FWB and 5 companies listed on the GPW. In the paper, the deductive method, assisted by literature studies and comparison induction was used. The areas of socially responsible activities undertaken by selected companies were presented and the range of their communication was assessed. Today, the TSL industry is characterized by high dynamics. Therefore, it is worth considering changing the current practices in the presentation of CSR activities of companies listed on the GPW. A proposal to change the current practices in this area was presented.(original abstract)